Extended High Frequency Audiometry in Polycystic Ovary Syndrome - Cuneyt Kucur; Suna Kabil Kucur; Ilay Gozukara; Ali Seven; Kadriye Beril Yuksel; Nadi Keskin; Fatih Oghan (The Scientific World Journal)
Objective. Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder affecting 5–10% of women in reproductive age. Insulin resistance, dyslipidemia, glucose intolerance, hypertension, and obesity are metabolic disorders accompanying the syndrome. PCOS is a chronic proinflammatory state and the disease is associated with endothelial dysfunction. In diseases with endothelial damage, hearing in high frequencies are mostly effected in early stages. We evaluated extended high frequency hearing loss in PCOS patients. Material Methods. Forty women diagnosed as PCOS and 25 healthy controls were included in this study. Age and BMI of PCOS and control groups were comparable. Each subject was tested with low (250–2000 Hz), high (4000–8000 Hz), and extended high frequency audiometry (8000–20000). Hormonal and biochemical values including LH, LH/FSH, testosterone, fasting glucose, fasting insulin, HOMA-I, and CRP were calculated. Results. PCOS patients showed high levels of LH, LH/FSH, testosterone, fasting insulin, glucose, HOMA-I, and CRP levels. The hearing thresholds of the groups were similar at frequencies of 250, 500, 1000, 2000, and 4000 Hz; statistically significant difference was observed in 8000–14000 Hz in PCOS group compared to control group. Conclusion. PCOS patients have hearing impairment especially in extended high frequencies. Further studies are needed to help elucidate the mechanism behind hearing impairment in association with PCOS.